Nationalism in Indonesian Literature as Active Learning Material - Ismawati, Esti (International Journal of Active Learning, 2018)
This research purpose was to identify and to find elements of nationalism in Indonesian literary works as teaching materials. The research method was descriptive inferential. Indonesian literary works that were identified included literary works of Balai Pustaka, Pujangga Baru, 1945, 1966, and the contemporary. From the results of the study, it could be concluded that the work of Indonesian literature since the Dutch colonial era ranging from Balai Pustaka to the work of literature nowadays (contemporary) contained the values of nationalism. It can be concluded that the values of nationalism in Indonesian literary works emerged since the Dutch colonial era, although they were symbolic. Along with the growing values of nationalism among Indonesian youth, even in the literary works the values appeared more explicit, more daring, and not just symbolic. These results need to be taught to SLA students using active learning. This research recommended the need for easy-to-digest nationalism teaching materials in order to realize the character of nationalism among learners.